A Qualitative Systematic Review of Women's Experiences Using Contraceptive Vaginal Rings: Implications for New Technologies. Issue 2 (20th May 2019) - Vargas, Sara E.; Midoun, Miriam M.; Guillen, Melissa; Getz, Melissa L.; Underhill, Kristen; Kuo, Caroline; Guthrie, Kate M.; ,
Abstract : CONTEXT: Vaginal rings are available for contraception and hormone replacement, and are being developed as HIV/STD or multipurpose prevention technologies. A comprehensive understanding of women's expectations of and experiences with rings is urgently needed to inform product development and to optimize ring use. METHODS: Three databases (PubMed, Global Health and CINAHL) were searched for English‐language, peer‐reviewed articles published between January 1996 and November 2017 that reported qualitative data on barriers to and facilitators of use of female‐controlled contraceptive methods. Data on study methods, findings and conclusions pertaining to contraceptive rings were extracted, organized and analyzed. RESULTS: Twenty‐six articles, all published since 2008, met the inclusion criteria. Seven studies focused largely or entirely on rings (and involved current, former or potential users), while the others focused on other contraceptive methods but included ring‐specific data. Familiarity with the ring was low, and women commonly had initial concerns about the method—often related to insertion and removal, cleanliness and discomfort with touching their vagina—that were typically overcome over time. Other major themes were issues related to ring use and discontinuation, the importance of ring‐related properties and characteristics, and considerations related to sexual partners and health care providers. CONCLUSIONS: Qualitative data have the potential to inform ring design and promotion. Future research should further explore women's expectations and experiences with the ring, the value of involving male partners in ring evaluation, and evaluation of interventions to improve patient–provider communication concerning ring choice and use.